Eye on Music Reading: A Methodological Review of Studies from 1994 to 2017 - Marjaana Puurtinen (Bern Open Publications, 2022)
In this review, we focus on the methodological aspects of eye-tracking research in the domain of music, published and/or available between 1994 and 2017, and we identify potentially fruitful next steps to increase coherence and systematicity within this emerging field. We review and discuss choices of musical stimuli, the conditions under which these were performed (i.e. control of performance tempo and music-reading protocols), performer’s level of musical expertise, and handling of performance errors and eye-movement data. We propose that despite a lack of methodological coherence in research to date, careful reflection on earlier methodological choices can help in formulating future research questions and in positioning new work. These steps would represent progress towards a cumulative research tradition, where joint understanding is built by systematic and consistent use of stimuli, research settings and methods of analysis.